1990
DOI: 10.1111/j.1365-2133.1990.tb08238.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma: aetiological importance of individual pigmentation and sun exposure

Abstract: A case-control study of cutaneous malignant melanoma (CMM) was based on 523 incident cases and 505 age- and sex-matched controls selected from the general population. The purpose was to investigate the relative risk of developing CMM associated with different sun habits and indicators of pigmentation, such as skin type, eye colour and hair colour. Compared to people with black hair, blonde subjects had a relative risk of 74.4 (95% confidence interval, 45.8-120.8). Associations with skin type and eye colour wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
1
4

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(64 citation statements)
references
References 14 publications
1
58
1
4
Order By: Relevance
“…Using sunscreen never or rarely at home under the age of 5 years (as reported by the parent) was associated with a doubling of risk, however, the association was not apparent when sunscreen use was assessed during holidays during the same time period. Although 1 case-control study of melanoma in young females 31 has reported a more than 2-fold increased risk for infrequent or no use of sunscreen, others have reported increased risk associated with sunscreen use 11,[32][33][34][35] including use in childhood 11,32 and this issue remains contentious. In the present study, it is not possible to check a parent's response against the child's response for the youngest time periods.…”
Section: Discussionmentioning
confidence: 99%
“…Using sunscreen never or rarely at home under the age of 5 years (as reported by the parent) was associated with a doubling of risk, however, the association was not apparent when sunscreen use was assessed during holidays during the same time period. Although 1 case-control study of melanoma in young females 31 has reported a more than 2-fold increased risk for infrequent or no use of sunscreen, others have reported increased risk associated with sunscreen use 11,[32][33][34][35] including use in childhood 11,32 and this issue remains contentious. In the present study, it is not possible to check a parent's response against the child's response for the youngest time periods.…”
Section: Discussionmentioning
confidence: 99%
“…Eight epidemiologic studies have reported that regular use of sunscreens is associated with significantly increased risk of melanoma (19,(47)(48)(49)(50)(51)(52)(53). The association persisted after controlling for the amount of time spent in the sun, skin type, and other predisposing factors, including history of sunburns.…”
Section: Discussionmentioning
confidence: 99%
“…The association persisted after controlling for the amount of time spent in the sun, skin type, and other predisposing factors, including history of sunburns. Five of these studies reported higher risk of melanoma associated with use of sunscreens in both sexes (19,49,50,52,53), while three reported the association in men (47,48,51). Another study reported a higher incidence of nevi, pigmented benign lesions of the epidermis that are associated with increased risk of melanoma, in children whose parents regularly applied sunscreens to the children's skin when outdoors in the sun (43).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who easily burn and tan poorly are at increased risks. This characteristic was a significant risk factor in all the studies examining sun sensitivity (17,18,20,21,23,27,29,31,32). However, the skin reaction to sunlight is also related to light pigmentation, freckling, and naevi (23, 32) and there seems to be an interaction between the influence of these…”
Section: Host F K I O R Smentioning
confidence: 99%